A Low-Barrier Approach to Developing Validated Chemistry Animations the Case of Chemical Bonding and Canva - iche Azani; Hamdil Mukhlisin; Rizmanhardian Ashari Kurniawan (Postgraduate, University of Mataram, 2025)
Chemistry education still faces serious challenges in integrating three levels of representation, namely macroscopic, microscopic, and symbolic. This difficulty becomes more complex in abstract topics such as chemical bonding, which requires students to relate real phenomena to invisible molecular processes and formal chemical symbols. Conventional learning media tend to be static, making them less capable of depicting particle dynamics, which ultimately leads to conceptual misunderstandings. This study aims to develop and validate animation-based learning media as an innovative solution to bridge these limitations. The method used is Design-Based Research (DBR) with a 4D development model (Define, Design, Develop, Disseminate). The research subjects involved a panel of experts consisting of material, language, and media validators, as well as 35 tenth-grade students at MAN 3 Pontianak. The validation results showed a high level of reliability with Aiken scores of 93% (material), 91% (language), and 87% (media), respectively. The classroom feasibility test obtained an average score of 90%, which is classified as “very good.” Thus, the animated video developed using the Canva application proved to be effective, affordable, and provided a systematic framework that can be replicated to teach abstract chemistry concepts more comprehensively.